Are phthalate ester contaminants in northern fulmar preen oil higher in birds that have ingested more plastic?. (January 2020) - Provencher, J.F.; Avery-Gomm, S.; Braune, B.M.; Letcher, R.J.; Dey, C.J.; Mallory, M.L.
Abstract: Understanding the impacts of plastic pollution is a global research priority. Previous research has shown that plasticizers such as phthalate esters detected in seabird tissues can be useful non-lethal biochemical markers of plastic ingestion as compared with more standard necropsy techniques. We examined the concentrations of six phthalate esters in the preen oil of Northern Fulmars ( Fulmarus glacialis) in relation to their retained plastics. Contrary to a previous study, we found that the phthalates examined were not analytically detectable in fulmar preen oil. Given that the birds we examined had up to 100 pieces of plastics in their stomachs, and all uropygial glands were completely emptied during the necropsies, it does not appear that measuring phthalates in preen oil of Northern Fulmars is a useful, non-lethal technique to determine if individuals ingest plastics, at least not currently given the available commercial analytical detection limits. Graphical abstract: Image 1 Highlights: Tools for non-lethal detection of ingested plastics in biota are needed. Phthalate esters may be useful indicators of plastics but need to be validated across species. We found no detectable levels of 6 phthalate esters in 10 northern fulmars with ingested plastics. Phthalate esters are unlikely to be useful indicators of plastic ingestion in seabirds.